(untitled) (TAMADDUN NURI JURNALI, 2024)
The author’s motive is to identify and study psycholinguistic equivalence in the context of translation science. The author seeks to broaden the understanding of this field by drawing attention to the importance of studying psycholinguistics in the context of translation. The title of the study indicates that particular attention is being paid to the psycholynguistic equivalence of the author’s IT motif in the translation of the text, which indicates the author’s desire to deepen this particular aspect and expand his knowledge in this field.